The Role of Traditional Markets in Improving the Community's Economy amid the Covid 19 Pandemic, Palangka Raya - Rinto Alexandro; Tonich Uda; Selvi Selvi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Economic development carried out by the Indonesian people is one of the efforts to create community welfare. Economic development that is being intensively carried out at this time is revitalizing a number of traditional markets which are the identity of a city. Traditional markets have an important role in helping the community's economy, especially for the middle class. Traditional markets are places for traders to peddle and promote agricultural products, livestock, plantations, craftsmen, or other producers as suppliers. Traditional markets are markets that are managed by the city government. Currently, traditional markets have become a new cluster for the spread of COVID-19. But people continue to carry out economic activities as usual. The purpose of this study is to find out how the role of traditional markets in improving the community's economy in the midst of the covid 19 pandemic, Palangka Raya city. The research methods used are: descriptive qualitative research and the nature of the research is qualitative research. Data collection techniques are: observation, interviews, and documentation. Data analysis techniques are: data reduction, data presentation, and drawing conclusions. The validity of the data is using: credibility, transferability, dependability, and confirmability. Based on the results of the research analysis, it can be concluded that: 1) The role of Traditional Markets for traders is as a place to market goods, promote local products, as well as for the development of traditional businesses. 2) The role of traditional markets for buyers is as a place to get daily necessities. 3) The Role of Traditional Markets for Development, namely through taxes and levies the management is able to build a better place for market buildings and assist regional development. 4) The role of traditional markets for human resources is to absorb workers in the informal sector. 5) The role of Traditional Markets for the government is to bring in foreign exchange for the State.